(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
in the process of training young volleyball players, especially at the initial training stage, the improvement of the effectiveness of using traditional and non-traditional exercises and action games that develop agility is highlighted.